Exploration of the Utilization of "LAYAR" as a Means of Assessment of Dentistry Education during the Covid-19 Pandemic - Prastiyani, Nur HN; Pratiwi, Alisa N (YARSI Dental Journal, 2024)
Introduction: The pandemic of COVID-19 has impacted all areas of life, as well as in education. Learning and evaluation of learning (assessment) outcomes must be transformed into online methods. Faculty of Dentistry Universitas YARSI used YARSI e-learning (LAYAR) as the most widely used media in the assessment of distance learning outcomes. Objective: This study aimed to explore the learners' perceptions related to the experience of using LAYAR as an assessment media during distance learning period at Faculty of Dentistry Universitas YARSI. Material and Methods: The study used a qualitative method with a phenomenological approach. Data collection was conducted through FGD (Focus Group Discussion) with academic and clinical stage students. The results of FGDs were written in the form of verbatim transcripts and then thematic analysis was carried out. Results: FGDs were conducted with 2 groups of academic stage students consisting of 8 students each and 1 group of clinical stage students consisting of 8 students. Three main themes were identified: the utilization of LAYAR, the assessment method used during distance learning through LAYAR, and the constraints of using LAYAR in the assessment. Conclusion: The use of LAYAR as an assessment media is considered quite user friendly but the limitation of the range of questions needs to be reviewed. The clinical stage students feel that the utilization of LAYAR was still insufficient. In addition, it was necessary to further utilize LAYAR for formative assessments that can further help students' understanding of learning.